The effect of expanded glass and polystyrene waste on the properties of lightweight aggregate concrete. Issue 1 (2nd January 2016) - Šeputytė-Jucikė, Jurga; Sinica, Marijonas
Abstract: The main objective of this study is to create a lightweight aggregate concrete (LWAC) with a low thermal conductivity coefficient using expanded glass (EG) aggregate, produced from waste glass or crushed expanded polystyrene waste, obtained by crushing waste packing tare of household appliances. Research related to the effects of the amount of Portland cement (PC) as well as EG aggregates and crushed expanded polystyrene waste on physical (density, thermal conductivity coefficient, water absorption and capillary coefficient) and mechanical (compressive strength) properties of LWAC samples are provided. Insulating LWAC based on a small amount of PC and lightweight EG aggregates and crushed expanded polystyrene waste, with especially low thermal conductivity coefficient values (from 0.070 to 0.098 W/ (m·K)) has been developed. A strong relationship between thermal conductivity coefficient and density of LWAC samples was obtained. The density of LWAC samples depending on the amount of PC ranged between 225 and 335 kg/m 3 . A partial replacement of EG aggregate by crushed expanded polystyrene waste, results in relative density decrease of LWAC samples. In LWAC samples the increased amount of PC results in increased compressive strength.